Enantioselective synthesis of pyrro[3, 4-c]quinoline pseudo-natural products. (20th July 2021) - Liu, Jie; Otte, Felix; Strohmann, Carsten; Waldmann, Herbert
Graphical abstract: Pyrro[3, 4- c ]quinoline pseudo-natural products were synthesized via asymmetric 1, 3-dipolar cycloaddition between amino acid-derived azomethine ylides and α, β-unsaturated malonic acid esters to yield pyrrolidines followed by a sequence of protection-, reduction- and lactamization steps. Highlights: Unprecedented recombination of pyrrolidine and tetrahydroquinoline. Highly enantioselective intermolecular 1, 3-dipolar cycloaddition. Tandem reduction and regioselective lactamization. Concise synthesis of pyrroquinoline pseudo-natural products. Abstract: Pseudo natural products (PNPs) are natural product-inspired compounds obtained by unprecedented combination of natural product (NP) fragments in complexity-generating transformations. The pyrrolidine- and tetrahydroquinoline fragments individually occur in numerous NPs with diverse bioactivity, yet not in combination. Herein we report the enantioselectively catalyzed asymmetric synthesis of pyrro[3, 4- c ]quinoline pseudo-natural products in which these two fragments are combined. The synthesis includes a highly enantioselective 1, 3-dipolar cycloaddition between amino acid-derived azomethine ylides and α, β-unsaturated malonic acid esters to yield pyrrolidines followed by a sequence of protection-, reduction- and lactamization steps.